The values of a and b in the given surd expression are; a = 27/22 and b = 1/2
The correct expression is;
(7 + √5)/(7 - √5) - (7 - √5)/(7 + √5) = a + (7/11)√5b
Let us first rationalize the denominator of the first term to get;
(7 + √5)/(7 - √5) = [(7 +√5)/(7-√5)] * [(7 + √5)/(7 + √5)]
⇒ (54 + 14√5)/44
⇒ (27/22) + 7(√5)/22
Let us first rationalize the denominator of the second term to get;
[(7 - √5)/(7 + √5)] * [(7 - √5)/(7 - √5)]
⇒ (54 - 14√5)/44
⇒ (27/22) - 7(√5)/22
Thus;
a = 27/22 and b = 1/2
Read more about surds at; https://brainly.com/question/24700530
#SPJ1